Archaeology along the Hålogaland Road: Combined results from the Archeological investigations 2020-2022. - Oppvang, Janne; Bruun, Inga Malene; Kjellman, Erik (Tromura, 2025)
Full text format of the report"Archaeology along the Hålogaland Road" has conducted archaeological investigations at 32 sites. The sites primarily encompass the periods of the Early and Late Stone Age, as well as Sami cultural heritage. The Bronze Age, Iron Age, and Middle Ages are represented by a few sites.From both the Early and Late Stone Age, we have examined several settlements, as well as other types of sites such as hunting stations. Many of the settlements from both periods feature house remains and cleared surfaces, and several of these show signs of being used repeatedly. Flint was the most important raw material during the Early Stone Age, while slate became central in the Late Stone Age. The sites appear to have been focused on the exploitation of marine resources. Among the findings, we particularly highlight the rich collection of axes and flakes from the Early Stone Age, where the flakes, among other things, indicate eastern connections. while single-edged knives, slate points, and several large grindstones are notable from the Late Stone Age. Numerous fishing sinkers have also been found throughout the period, one of which features an engraved figure.The Sami sites are dated from the Middle Ages up to the 20th century and include structures such as turf huts, a smithy, stone fences, and a tent settlement. These sites represent both the coastal Sami and reindeer-herding Sami cultures in the region, utilizing both marine and land-based resources. The findings primarily come from the two sites Kåringskrysset and Nesset Kobbenesset and include items such as boat nails, a padlock, window glass, cutlery, anvil stones, baking stones, ceramics, fire flint, and slag.
Keywords: Archaeology; Archaeological excavation; Early stone age; Mesolithic; Late Stone Age; Neolithic; Iron Age; Middle Ages; medieval period; Modern times; Sami cultural heritage; dwellings; habitation site; turf hut remains; smithy; forge; hunting station; stone fence; settlement; tent; árran (Sámi hearth); álvi (Sámi forge); flint; slate; quartzite; quartz; chert; pumice; clay; daub; iron nails; fire flint; fishing sinkers; ceramics; anvil stone; baking stone; grinding stone; flakes; knives; blades; cores; arrowheads; spearheads; dagger; single-edge knife